Optimized Pond Structure for Catfish Farming as a Permanent Revenue Source of Ahmad Dahlan Muhammadiyah Reformatory - Sudarisman, S.; Suwanda, Totok (Politeknik Harapan Bersama, 2023)
This community service activity was conducted in accordance with the problems faced by the reformatory, i.e. lack of revenue source to fund its regular activities, and aims to providing catfish farming ponds which can be used for life skill training medium for reformatory students and a permanent source of income for the reformatory. Having had this ponds the reformatory has an additional permanent revenue source, in addition, the ponds was constructed by optimizing the potential mechanical properties of the material being used. The methods used include object observation, interviews with reformatory management, technical guidance, and catfish farming practices. The result of this activity is the availability of three tarpaulin catfish ponds measuring 3 ´ 2 m2 each which can be used by the reformatory students as a medium for life skills training. The time for putting baby fish into the three ponds was scheduled in different times so that the harvest time would also be different such that market oversupply can be avoided. During the farming period, the reformatory students were very enthusiastic in feeding and monitoring the condition of the pond water and the growth of the catfish, so that catfish farming could run as expected. The first harvest was partly consumed and the other was sold to the local market.